For which natural number n is the following equality true?
k = 1 ∑ 2 n 2 2 n + 4 sin 2 ( 2 n + 2 2 π k − π ) 1 = 8 1
Bonus: Use this result to solve the Basel problem .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We will use induction on n. The base case of n=0 is straghtforward. For the iterative step, we will show that the k'th term out of
2
n
is equal to the k'th term out of
2
n
+
1
plus the
2
n
+
1
+
1
−
k
'th term out of
2
n
+
1
. In equation form, we must show that
2
2
n
+
4
sin
2
(
2
n
+
2
2
π
k
−
π
)
1
=
2
2
n
+
6
sin
2
(
2
n
+
3
2
π
(
2
n
+
1
+
1
−
k
)
−
π
)
1
+
2
2
n
+
6
sin
2
(
2
n
+
3
2
π
k
−
π
)
1
2
2
n
+
6
sin
2
(
2
n
+
3
2
π
(
2
n
+
1
+
1
−
k
)
−
π
)
1
+
2
2
n
+
6
sin
2
(
2
n
+
3
2
π
k
−
π
)
1
=
2
2
n
+
6
cos
2
(
2
n
+
3
2
π
k
−
π
)
1
+
2
2
n
+
6
sin
2
(
2
n
+
3
2
π
k
−
π
)
1
=
2
2
n
+
6
cos
2
(
2
n
+
3
2
π
k
−
π
)
sin
2
(
2
n
+
3
2
π
k
−
π
)
1
Using the double angle identity for sin(x), we can show that
2
2
n
+
4
sin
2
(
2
n
+
2
2
π
k
−
π
)
1
=
2
2
n
+
6
cos
2
(
2
n
+
3
2
π
k
−
π
)
sin
2
(
2
n
+
3
2
π
k
−
π
)
1
which gives us the desired result. By the way, this property is not specific to powers of 2. If we substitute n for
2
n
, the equality remains true; powers of 2 are just a lot easier to prove than the natural numbers.
Bonus: Because sum is equal to 1/8 for all n, we will consider the limit of each term in the sum as n goes to infinity. Using the Taylor series for sin(x), we obtain π 2 ( 2 k − 1 ) 2 + e 1 where e is a small error whose most significant term is proportional to 2 − 2 n . Notice that the amount of error shrinks more quickly than the number of terms ( 2 n ) that the error appears in grows. Therefore, since the limit as n goes to infinity of each individual term is π 2 ( 2 k − 1 ) 2 1 , the limit of the entire sum as n goes to infinity is k = 1 ∑ ∞ ( π 2 ( 2 k − 1 ) 2 1 ) Let the sum of the reciprocals of the squares (i.e. the Basel Problem) be S. Notice that S/4+ π 2 *(the infinite sum that we just created)=S. Substituting 1/8 for (the infinite sum that we just created) shows us that the sum of the reciprocals of the squares is equal to 6 π 2 .
Note: Some of you may be wondering why our error term had to shrink at a greater rate than the rate at which that the number of terms in the sum grew. Consider the sum k = 1 ∑ n 2 ( k 2 1 + n 1 ) Even though the limit as n goes to infinity of each individual term is 1 / k 2 , the error term of 1/n gets added n 2 times, so the limit of the entire sum is infinity, not 6 π 2 . Similarly, π 2 ( 2 k − 1 ) 2 + e 1 can be rearranged to show that not only does the error term tend to 0 for large n, but the sum of the differences( π 2 ( 2 k − 1 ) 2 + e 1 − π 2 ( 2 k − 1 ) 2 1 ) caused by all 2 n of the error terms tends to 0 also.
Problem Loading...
Note Loading...
Set Loading...
If we define S n = 2 2 n + 4 1 k = 1 ∑ 2 n c o s e c 2 ( 2 n + 2 ( 2 k − 1 ) π ) for any integer n ≥ 0 then S 0 = 1 6 1 c o s e c 2 4 1 π = 8 1 . Note also that S n = 2 2 n + 4 1 k = 1 ∑ 2 n c o s e c 2 ( 2 n + 2 ( 2 k − 1 ) π ) = 2 2 n + 4 1 k = 1 ∑ 2 n c o s e c 2 ( 2 n + 2 ( 2 ( 2 n + 1 − k ) − 1 ) π ) = 2 2 n + 4 1 k = 1 ∑ 2 n sec 2 ( 2 n + 2 ( 2 k − 1 ) π ) and so S n + 1 = 2 2 n + 7 1 k = 1 ∑ 2 n + 1 { c o s e c 2 ( 2 n + 3 ( 2 k − 1 ) π ) + sec 2 ( 2 n + 3 ( 2 k − 1 ) π ) } = 2 2 n + 7 1 k = 1 ∑ 2 n + 1 c o s e c 2 ( 2 n + 3 ( 2 k − 1 ) π ) sec 2 ( 2 n + 3 ( 2 k − 1 ) π ) = 2 2 n + 5 1 k = 1 ∑ 2 n + 1 c o s e c 2 ( 2 n + 2 ( 2 k − 1 ) π ) = 2 2 n + 5 1 k = 1 ∑ 2 n { c o s e c 2 ( 2 n + 2 ( 2 k − 1 ) π ) + c o s e c 2 ( 2 n + 2 ( 2 ( k + 2 n ) − 1 ) π ) } = 2 2 n + 5 1 k = 1 ∑ 2 n { c o s e c 2 ( 2 n + 2 ( 2 k − 1 ) π ) + sec 2 ( 2 n + 2 ( 2 k − 1 ) π ) } = 2 1 S n + 2 1 S n = S n and hence S n = 8 1 for all positive integers n .